2016
DOI: 10.1186/s12889-016-3683-8
|View full text |Cite
|
Sign up to set email alerts
|

Context matters! The relationship between mother-reported family nutrition climate, general parenting, food parenting practices and children’s BMI

Abstract: BackgroundEfforts to explain children’s nutrition behavior or weight often involve investigating the parent-child relationship, typically studying the associations between food parenting practices (FPPs) and child outcomes. However, these behaviors are embedded in a broader system: general parenting (GP, the general emotional climate at home), and the family health climate (an aspect of the broader family system in the context of health). In the current study, we combined the parent-child measures of parenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…Restriction was found to be associated with a favourable intake by older children and adolescents, if parents showed a general parenting style characterised by a combination of high nurturance and control (20)(21)(22) , or high nurturance only (23) . Healthy parenting practices had stronger positive effects when used within a positive general parenting context (24,25) . Availability had the strongest effect when parents scored high on control but lower on nurturance (22) .…”
mentioning
confidence: 99%
“…Restriction was found to be associated with a favourable intake by older children and adolescents, if parents showed a general parenting style characterised by a combination of high nurturance and control (20)(21)(22) , or high nurturance only (23) . Healthy parenting practices had stronger positive effects when used within a positive general parenting context (24,25) . Availability had the strongest effect when parents scored high on control but lower on nurturance (22) .…”
mentioning
confidence: 99%
“…Asking too many questions might prevent respondents from completing the questionnaire or lead to drop-out in longitudinal studies with follow-up measures, which is especially problematic in the case of selective drop-out. An example of the application of the CSPQ in the study of contextual factors in the parenting-food intake relationship is also available [ 42 ]. In that study, the CSPQ was applied to get a broader view of the relation between FPPs and other concepts, including general parenting.…”
Section: Discussionmentioning
confidence: 99%
“…Exploratory factor analyses resulted in four factors: healthy FPPs (6 items, Cronbach’s alpha = 0.85), covert FPPs (4 items, Cronbach’s alpha = 0.67), overt FPPs (2 items, Cronbach’s alpha = 0.70), and non-nutritive FPPs (2 items, Cronbach’s alpha = 0.54). The authors reported that “FPPs and child BMI-z scores were in the expected direction (i.e., healthy FPP were negatively related to BMI z-scores and non-nutritive FPPs were positively related to BMI z-score)” [ 42 ] (p. 8).…”
Section: Discussionmentioning
confidence: 99%
“…The FNC scale is a validated questionnaire [152], which was translated into Dutch [176]. It can be completed by one family member or by multiple family members, after which an aggregated FNC score can be calculated [152,177].…”
Section: Family Health Climatementioning
confidence: 99%
“…However, in reality, parents and children are part of a family in which family members influence each other's behaviors, indicating a reciprocal influence [175]. Focusing only on individual parenting practices and general parenting, and not considering this family-level influence can lead to important information being missed when studying the parents' influence on children's nutrition behavior [13,176].…”
Section: Introductionmentioning
confidence: 99%